Body Mobility and Attention Networks in 6- to 7-Year-Old Children - Rosenbaum, Joëlle; Hascoët, Jean-Michel; Hamon, Isabelle; Petel, Arthur; Caudron, Sébastien; Ceyte, Hadrien (Frontiers in Psychology, 2021)
Learning in 6 to 7-year-old children is strongly influenced by three functions of attention: alertness, orienting, and executive control. These functions share a close relationship with body mobility, such as the posture adopted or a request to stay still during tasks. The aim of this study (ClinicalTrials.gov - NCT 03125447) was to analyze the influence of body posture (standing versus sitting) and the influence of these imposed postures compared to a free body mobility on attention functions in 6 to 7-year-old children. Twenty-one children (11 girls) with a mean age of 6.7±0.6 years performed the Attention Network Test for Children in three body mobility conditions: sitting still, standing still, and free to move. Three attentional scores were calculated which would separately reflect performance of alertness, orienting and executive control. Overall, no difference in alertness performance was found between the three bodily mobility conditions. In addition, our results suggest a general poor orienting performance in children, whatever the body mobility condition, which might be related to their young age. Finally, children improved their executive control performance when they stood still, probably due to an improvement in arousal and mental state.